2009
DOI: 10.1172/jci37716
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylenimine-based siRNA nanocomplexes reprogram tumor-associated dendritic cells via TLR5 to elicit therapeutic antitumor immunity

Abstract: The success of clinically relevant immunotherapies requires reversing tumor-induced immunosuppression.Here we demonstrated that linear polyethylenimine-based (PEI-based) nanoparticles encapsulating siRNA were preferentially and avidly engulfed by regulatory DCs expressing CD11c and programmed cell death 1-ligand 1 (PD-L1) at ovarian cancer locations in mice. PEI-siRNA uptake transformed these DCs from immunosuppressive cells to efficient antigen-presenting cells that activated tumor-reactive lymphocytes and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
208
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(229 citation statements)
references
References 50 publications
11
208
2
2
Order By: Relevance
“…PEI is superior to other nonmicrobial transfection agents because of its ability to protect DNA from degradation [18], to escape intracellular endosomal lysis [19] and to efficiently deliver DNA into the nucleus of cells [20]. Formulation with PEI polymers has been employed in DNA-and siRNAbased immunotherapy against cancer [21,22] and in vaccination studies targeting different infectious agents [10,23,24].In the present study, we have evaluated the physicochemical characteristics of a series of PEI polymers and have assessed associations between particular characteristics of these polymers and their ability to facilitate in vivo DNA expression and enhanced adaptive immune responses. Moreover, we have examined plasmid DNA constructs formulated with these various PEI polymers for their ability to generate immune responses under conditions that maximize the immunogenicity of these PEI-DNA complexes.…”
mentioning
confidence: 99%
“…PEI is superior to other nonmicrobial transfection agents because of its ability to protect DNA from degradation [18], to escape intracellular endosomal lysis [19] and to efficiently deliver DNA into the nucleus of cells [20]. Formulation with PEI polymers has been employed in DNA-and siRNAbased immunotherapy against cancer [21,22] and in vaccination studies targeting different infectious agents [10,23,24].In the present study, we have evaluated the physicochemical characteristics of a series of PEI polymers and have assessed associations between particular characteristics of these polymers and their ability to facilitate in vivo DNA expression and enhanced adaptive immune responses. Moreover, we have examined plasmid DNA constructs formulated with these various PEI polymers for their ability to generate immune responses under conditions that maximize the immunogenicity of these PEI-DNA complexes.…”
mentioning
confidence: 99%
“…For example, linear PEI-based NPs encapsulating siRNA were used to silence PD-L1 expression on mouse tumor-associated DCs. 88 In addition, in this study linear PEI was identified as a novel TLR5 agonist and indicates that activation of TLR5 and TLR7 reversed the tolerogenic phenotype of human and mouse ovarian tumor-associated DCs. The results of this study demonstrated that transforming ovarian cancer-associated DCs in vivo from an immunosuppressive to an immunostimulatory and tumoricidal cell type is not only feasible using siRNA-PEI nanocomplexes, but also more effective against aggressive ovarian tumors than what previously reported synergistic effect of standard chemotherapies combined with DC depletion.…”
Section: Blockading the Pd-1/pd-l1 Pathwaymentioning
confidence: 61%
“…The results of this study demonstrated that transforming ovarian cancer-associated DCs in vivo from an immunosuppressive to an immunostimulatory and tumoricidal cell type is not only feasible using siRNA-PEI nanocomplexes, but also more effective against aggressive ovarian tumors than what previously reported synergistic effect of standard chemotherapies combined with DC depletion. 88 …”
Section: Blockading the Pd-1/pd-l1 Pathwaymentioning
confidence: 99%
“…The caveat of this approach is that, as commented above, a myriad of phagocytic cells with enhanced endocytic pathways are present in the microenvironment of virtually all solid tumors. Overcoming endocytosis by these abundant leukocytes and reaching cancer cells represents a barrier that, at least in our hands, has proven impossible (Cubillos-Ruiz et al, 2009a, 2009bCubillos-Ruiz et al, 2010). Nevertheless, the myeloid leukocytes that spontaneously take up particulate materials are also optimal targets for miRNA mimeticsbased interventions.…”
Section: Manipulation Of Microrna Activity In the Tumor Microenvironmmentioning
confidence: 99%